Production of Ni(OH)2 nanosheets by liquid phase exfoliation: From optical properties to electrochemical applications - COLEMAN, JONATHAN; DONEGAN, JOHN; NICOLOSI, VALERIA; LYONS, MICHAEL; DUESBERG, GEORG; MCEVOY, NIALL; GODWIN, IAN (My University, 2016)
Here we demonstrate that liquid phase exfoliation can be used to convert layered crystals of nickel hydroxide into Ni(OH)2 nanosheets in relatively large quantities and without the need for ion intercalation. While other procedures require harsh synthesis conditions and multiple reaction steps, this method involves ultrasonication of commercially available powders in aqueous surfactant solutions and so is relatively mild and potentially scalable. Such mild exfoliation is possible because the surface energy of Ni(OH)2, as measured by inverse gas chromatography, is relatively low at ∼70 mJ m−2, similar to other layered materials. TEM, AFM, XPS and Raman spectroscopy show the exfoliated nanosheets to be relatively thin (mean ∼10 monolayers thick) and of good quality. Size selection by liquid cascade centrifugation allowed the production of samples with mean nanosheet lengths ranging from 55 to 195 nm. Optical measurements on dispersions showed the optical absorption coefficient spectra to be relatively invariant with nanosheet size while the scattering coefficient spectra varied strongly with size. The resultant size-dependence allows the extinction spectra to be used to estimate nanosheet size as well as concentration. We used the exfoliated nanosheets to prepare thin film electrodes for use in supercapacitors and as oxygen evolution catalysts. While the resultant capacitance was reasonably high at ∼1200 F cm−3 (20 mV s−1), the catalytic performance was exceptional with currents of 10 mA cm−2 observed at overpotentials as low as 297 mV, close to the state of the art.
PUBLISHED
Export Date: 15 September 2016
Keywords: liquid phase exfoliation; liquid phase exfoliation; Nanoscience & Materials; Hydrogen; OXIDE SURFACES